Report on phylloplane mycoflora Associated with Catharanthus roseus (L.) G. Don A herbal medicinal plant in Bangladesh (Bangladesh Journal of Scientific Research, 2016)
Abstract not availableBangladesh J. Sci. Res. 27(2): 201-207, December-2014